Germany’s Strategic Activity in the Sahel and the Problem of Sovereignty for Regional States: The Case of Mali - Trunov Philipp Olegovich (Ученые записки Института Африки Российской академии наук)
Using Mali as an example of a geostrategically important African state, the article explores the extent to which Germany’s political and military steps contributed or did not contribute to the sovereignty of the state that was trying to overcome the instability. Taking into account the ambiguous issue of the completeness of the sovereignty of Germany itself, the author analyzes the FRG’s fundamental ability to transfer its experience in this field to other states. In the second half of the 2010s, the scope and effectiveness of German efforts to stabilize the situation in Mali were insufficient. Germany, especially in the first stages of the settlement (from 2013 to 2015), did not make a noticeable contribution to peacemaking and peacekeeping activities. The use of the Bundeswehr in the field became noticeable only from 2016–2018; however, it did not lead to the necessary results. By the mid-2010s, Germany had already begun to take an active part in the security sector reform in Mali. However, the qualitative and quantitative parameters of the newly trained personnel of the Malian army were insufficient to ensure peace and security in the country. Having accepted the functions of one of the main external participants in the settlement, Germany did not accompany this with the necessary efforts. In addition, Germany was not ready to ensure efficiently the nationalization of the settlement, that is, to transfer control over the process to those internal forces that were capable of leading the country to peace.